Modulation of gamma oscillations in the pedunculopontine nucleus by neuronal calcium sensor protein-1: Relevance to schizophrenia and bipolar disorder - D'Onofrio, Stasia (2015)
Reduced levels of gamma-band activity are present in schizophrenia and bipolar disorder patients. In the same disorders, increased neuronal calcium sensor protein-1 (NCS-1) expression was reported in a series of postmortem studies. These disorders are also characterized by sleep dysregulation, suggesting a role for the reticular activating system (RAS). The discovery of gamma-band activity in the pedunculopontine nucleus (PPN), the cholinergic arm of the RAS, revealed that such activity was mediated by high-threshold calcium channels that are regulated by NCS-1.We hypothesized that NCS-1 normally regulates gamma-band oscillations through these calcium channels and that excessive levels of NCS-1, such as would be expected with overexpression, decrease gammaband activity. We found that PPN neurons in rat brain slices manifested gamma-band oscillations that were increased by low levels of NCS-1 but suppressed by high levels of NCS-1.Our results suggest that NCS-1 overexpression may be responsible for the decrease in gamma-band activity present in at least some schizophrenia and bipolar disorder patients.